Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas pada UMKM Kota Pangkalpinang - Rulyanti Susi Wardhani; Dian P W; Darus Altin (Politeknik Negeri Sriwijaya, 2018)
The purpose of this study was to membukti whether the competence of human resources, commitment, use of information technology, education owner, and qualitative financial report on the implementation of Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) on SMEs in Pangkalpinang. Of the population, sampling be carried out so that the 100 respondents who then performed the sampling cluster sampling. The results showed formed two factors, namely first is qualitative financial statements and the second factor is the education of the owner. Lowest variable is socialization, it obtained information from respondents who claimed to have been entirely done about SAK ETAP dissemination of relevant parties such as the Department of Industry, Trade, Cooperatives and SMEs Pangkalpinang, Universities, and the Indonesian Institute of Accountants ( IAI) Territory of the Pacific Islands.